Micah : a commentary - Wolff, Hans Walter (Continental commentaries., 1990)
Wolff's commentary on Micah is one of the most thorough works available in English. His insightful observations on the message of the prophet make this book a standard commentary on Micah for years to come. It is highly recommended to scholars, ministers, and theological students as an indispensable aid.